Appropriate Information for meaningful appropriation: An attempt to understand the relevance and veracity of Health Communication in Social Media - S. Augustin Jesuvadian; S. G. Veeralakshmanan; Gnana D Hans (The Bioscan, 2025)
The rise of modern social media platforms has revolutionizedinformation sharing, notably in health communication. This studyaimed to explore the widespread adoption of new media for health-related enquiries, communication, and advice-seeking. It aims to assess the credibility of health information disseminated through social media and its increasing use for general health queries and specific conditions. Employing a comprehensive mixed-methods approach, this study aims to identify the factors that drive individuals’ engagement with digital platforms related to health issues. It holds promise for illuminating the influence of social and new media on public health discourse and individuals’ verification practices. KEYWORDS Health communication, social media, health information, fact-checking.